1998
DOI: 10.1038/sj.onc.1202581
|View full text |Cite
|
Sign up to set email alerts
|

Caspases: the proteases of the apoptotic pathway

Abstract: Apoptosis, a morphologically defined form of physiological cell death, is implemented by a death machinery whose executionary arm is a family of cysteine proteases called caspases. These death proteases are part of a proteolytic caspase cascade that is activated by diverse apoptotic stimuli from outside and inside of the cell. The cell death machinery is evolutionarily conserved and composed of caspases and their regulatory components that include activators and repressors. These key components of the death ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
614
0
11

Year Published

1999
1999
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 953 publications
(646 citation statements)
references
References 92 publications
(136 reference statements)
21
614
0
11
Order By: Relevance
“…24 As expected, treatment with AP20187 did not cause processing of endogenous caspase-3 in HDMECs transduced with control viruses (Figure 3a). In contrast, HDMEC-…”
Section: Dimerization Of Icaspase-9 Induces Activation Of Endogenous supporting
confidence: 74%
See 1 more Smart Citation
“…24 As expected, treatment with AP20187 did not cause processing of endogenous caspase-3 in HDMECs transduced with control viruses (Figure 3a). In contrast, HDMEC-…”
Section: Dimerization Of Icaspase-9 Induces Activation Of Endogenous supporting
confidence: 74%
“…These results are consistent with previous observations that showed that factors such as VEGF promote endothelial cell survival by acting on various molecules including Bcl-2 and Akt, [2][3][4] that are known to function upstream of caspase-9 in the apoptosis pathway. 24 Most anti-angiogenic strategies currently in clinical trials are based on the delivery of antibodies or drugs that inhibit endothelial cell-specific survival signals and promote apoptosis by a default mechanism. In these approaches, the therapeutic agents are inherently targeted to the endothelium, but most of these agents induce moderate levels of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was also speci®c to this antibody as not reproduced with anti-p110b or anti-p110g antibody. Finally antip110a-induced cell death was reversed when pretreating cells with 0.1 mM z-VAD-fmk, a general inhibitor of proteases of the caspase family, known to mediate apoptotic signals (Nunez et al, 1998). From these data, we concluded that PI3Ka plays an important role in carcinoma cell survival.…”
Section: Brdu Incorporation (%)mentioning
confidence: 80%
“…caspase-8) and executor (e.g. caspase-3), based on their roles in the apoptotic signalling cascade (Salvesen and Dixit, 1997;Nunez et al, 1998). Depending on apoptotic signal and cell type, activation of initiator caspases may lead to mitochondria-dependent and/or -independent activation of executor caspases; whereas the former requires cytochrome c release and activation of caspase-9 as consequences of mitochondria damage, the latter is characterised by a cytochrome-c-and caspase-9-independent activation of executor caspases (Krammer, 2000).…”
Section: Discussionmentioning
confidence: 99%